GROWTH, YIELD AND VARIANCE COMPONENTS OF WATERMELON (Citrullus lanatus) GROWN ON LIME (CaCO3)-AMENDED ACIDIC SOIL OF SOUTH-EASTERN NIGERIA: GROWTH, YIELD AND VARIANCE COMPONENTS OF WATERMELON (Citrullus lanatus) GROWN ON LIME (CaCO3)-AMENDED ACIDIC SOIL OF SOUTH-EASTERN NIGERIA - OBOK, EKEMINI EDET; Ekpiken, Francis; Akpan, Joyce; Nwagwu, Francis; Ittah, Macauley; Uwah, Donatus (Journal of Agricultural Sciences (Belgrade), 2023)
A field experiment was conducted to assess growth and yield responses of watermelon to lime application in acid soil of Calabar. The experiment was a 3 × 3 factorial in a randomized complete block design (RCBD) with three replications. Varietal differences (Heracles F1, Kaolack and Sugar Baby), lime (CaCO3) rates (0 t ha-1, 2.7 t ha-1 and 5.7 t ha-1) and their interactions effect on growth and yield traits of watermelon were studied. Heracles F1 and Kaolack outperformed Sugar Baby (p ≤ 0.05) in growth and yield. Lime rates 2.7 t ha-1 and 5.7 t ha-1 increased the initial soil pH (4.6) by 21.74 % and 43.48 %, respectively. Vine length, number of leaves, transverse and longitudinal sections of the fruits and sugar content of the fruits had ≥ 50 % heritability, a useful index in the selection of choice growth and yield traits in watermelon. Multi-location studies are recommended to give further insights to this pilot study.